The cross-talk between canonical and non-canonical Wnt-dependent pathways regulates P-glycoprotein expression in human blood-brain barrier cells (2014)
In this work, we investigate if and how transducers of the 'canonical' Wnt pathway, i.e., Wnt/glycogen synthase kinase 3 (GSK3)/?-catenin, and transducers of the 'non-canonical' Wnt pathway, i.e., Wnt/RhoA/RhoA kinase (RhoAK), cooperate to control the expression of P-glycoprotein (Pgp) in blood-brain barrier (BBB) cells. By analyzing human primary brain microvascular endothelial cells constitutively activated for RhoA, silenced for RhoA or treated with the RhoAK inhibitor Y27632, we found that RhoAK phosphorylated and activated the protein tyrosine phosphatase 1B (PTP1B), which dephosphorylated tyrosine 216 of GSK3, decreasing the GSK3-mediated inhibition of ?-catenin. By contrast, the inhibition of RhoA/RhoAK axis prevented the activation of PTP1B, enhanced the GSK3-induced phosphorylation and ubiquitination of ?-catenin, and reduced the ?-catenin-driven transcription of Pgp. The RhoAK inhibition increased the delivery of Pgp substrates like doxorubicin across the BBB and improved the doxorubicin efficacy against glioblastoma cells co-cultured under a BBB monolayer. Our data demonstrate that in human BBB cells the expression of Pgp is controlled by a cross-talk between canonical and non-canonical Wnt pathways. The disruption of this cross-talk, e.g., by inhibiting RhoAK, downregulates Pgp and increases the delivery of Pgp substrates across the BBB. © 2014 ISCBFM.